Edmund Siemers. Unternehmer und Stifter - Gerhardt, Johannes (Mäzene für Wissenschaft, 2014)
As a creative entrepreneur, Edmund Siemers was one of the pioneers of petroleum trading in Germany. Later he succeeded as importer of Chilean nitre and built up his own fleet of ships. Finally he became a builder and landowner in the north of Hamburg. However, Edmund Siemers became really famous for his two large foundations: in 1896 Edmundsthal-Siemerswalde in Geesthacht, one of the first pulmonary treatment centres in Germany, and in 1907 the lecture building on the Moorweide, still a symbol of "the University" in Hamburg.Edmund Siemers' life is equally linked to the Hamburg, German and Transatlantic economic history of the 19th and early 20th centuries. He embodies a donor from Hamburg's upper middle classes in an ideal-typical manner. This is the first biography of "Hamburg's Carnegie", who also appeared as a donor and member of the board of trustees of the Hamburg Scientific Foundation.